Art, Shamanism and Animism - Wallis, Robert J.; Carocci, Max (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Art, shamanism, and animism are mutable, contested terms which, when brought together, present a highly charged package. Debates around these three terms continue to generate interest and strong opinions in the first decades of the twenty-first century. The editors recognise the urgency to explore them together in an unprecedented exercise which, to date, has only been attempted with reference to selected disciplines, periods, or regions. The contributors to this collection reignite debates around the status of 'things' identified as 'art' through the lens of theories drawn from new materialism, new animism, and multi-species and relational thinking. They are concerned with how and when art-like things may exceed conventional understandings of 'art' and 'representation' to fully articulate multiple scenarios or 'manifestations' in which they interface with academic discourses around animism and shamanism. The authors put in sharp focus the materiality of art-things while stressing their agentive, emotive, and performative aspects, looking beyond their appearances to what they do and who they may be or become in their dealings with diverse interlocutors. The contributors are united in their recognition that things and images are deeply entangled with how different communities, human and other-than-human, experience life, shifting attention from an obsolete concept of worldview to how reality is perceived through all the senses, in all its aspects, both tangible and intangible.